Prevention and Treatment of Reproductive Tract Infection - Risnawati Ramli (Newinera Publisher, 2020)
Reproductive Tract Infections (ISR) occur because of the process of entering and breeding the germs that cause infections into the female reproductive tract. Caring for sexual organs is often not done as often as caring for other organs. Though sexual organs need extra attention. In these sexual organs, the resulting sweat is quite excessive. So that the sexual organs become moist. prevention that can be done to prevent the occurrence of sexually transmitted diseases that is with care and maintain the cleanliness of the reproductive organs. Treatments that can be done are consuming healthy and nutritious eating, avoid using tight pants, check with your doctor if you experience vaginal discharge for a very long time, make it a habit to cleanse the genitals after sexual intercourse, do not use pantyliner, avoid having sexual intercourse with multiple partners. Washing the genitals every day, changing clothes frequently, at least twice a day in the bath, during menstruation, use soft pads, always wash hands before touching the genitals, avoid using other people's towels or washcloths and shave a portion of pubic hair to prevent bacterial growth